Probing the Lewis Acidity and Catalytic Activity of the Metal-Organic Framework [Cu3(btc)2] (BTC=Benzene-1,3,5-tricarboxylate) - Alaerts, Luc; Séguin, Etienne; Poelman, Hilde; Thibault-Starzyk, Frédéric; Jacobs, Pierre A.; De Vos, Dirk E. (Chemistry : a European journal, 2006)
An optimized procedure was designed for the preparation of the microporous metal–organic framework (MOF) [Cu3(btc)2] (BTC=benzene‐1,3,5‐tricarboxylate). The crystalline material was characterized by X‐ray diffraction, optical microscopy, SEM, X‐ray photoelectron spectroscopy, N2 sorption, thermogravimetry, and IR spectroscopy of adsorbed CO. CO adsorbs on a small number of Cu2O impurities, and particularly on the free CuII coordination sites in the framework. [Cu3(btc)2] is a highly selective Lewis acid catalyst for the isomerization of terpene derivatives, such as the rearrangement of α‐pinene oxide to campholenic aldehyde and the cyclization of citronellal to isopulegol. By using the ethylene ketal of 2‐bromopropiophenone as a test substrate, it was demonstrated that the active sites in [Cu3(btc)2] are hard Lewis acids. Catalyst stability, re‐usability, and heterogeneity are critically assessed. A systematic study of the catalytic properties of a metal‐organic framework: [Cu3(btc)2] is a very selective catalyst for specific isomerizations of terpenes, terpene epoxides, and ketals (see scheme). Together with IR spectroscopic measurements on adsorbed probe molecules, this proves the hard Lewis acid properties of the material.